Safety and immunogenicity of the DTP/HB /Hib combination vaccine: phase I study - Kusnandi Rusmil; Eddy Fadlyana; Novilia Sjafri Bachtiar; Hadyana Hadyana (Indonesian Pediatric Society Publishing House, 2013)
Background The World Health Organization (WHO) has recommended the introduction ofhepatitis B (HB) and Haemophilus influenza type b (Hib) vaccines into routine childhood vaccination programs. A new diptheria/tetanus/pertussis (DTP) /hepatitis B/Hib pentavalent combination vaccine has been developed. Objective To evaluate the safety and immunogenicity of a new combination DTP/HB/Hib liquid vaccin e in infants. Met hods An open-label, uncontrolled, prospective intervention phase I study was con ducted on 30 healthy infants aged 6- 11 weeks. Each subject received 3 doses of DTP/HB/Hib vaccine, formulated by Bio Fanna, 0.5 mL intramuscularly at the left anterolateral thigh region using a 25-gauge n eedle of 25 mm length . Subjects were followed for 1 month after administration of each vaccine dose to evaluate its safety, while serum anti-diphteria, tetanus, HB, Hib, and per tussis antibodies were measured prior to the l '' dose and 1 month after the Jtd dose. Results Among 30 vaccinated subjects, 18 infants had fever within 24 hours after the first vaccination. Most cases of fever were mild in intensity and resolved within 24 hours. No other systemic or local reactions, or serious adverse events were observed in our subjects during the study. The immunogenicity results after Jtd vaccine dose showed that the geometric mean titer of the antipolyribosylribitol phosphate (PRP) antibody levels increased significantly from 0.0041μ,g/mL to 4.3 7 μ,g/mL after vaccination, and most infants h ad a fourfo ld or greater rise in antibody levels over their pre-injection levels . All subjects who received DTP/ HB/Hib liquid vaccine had seropro tective antibodies against tetanus, diphtheria,a and hepatitis B, while 29/30 infants had seroprotective antibodies against pertussis. Conclusion This new diphtheria/tetanus/pertusis/hepatitis B/Hib combination vaccine has excellent safety profile and antibody responses in infants. These results encourage further clinical evaluation in phase II.